Growth comparison of Acanthamoeba genotypes T3 and T4 in several culture media - Latifi, Alireza (Heliyon, 2020)
Acanthamoeba causes severe diseases such as Granulomatous Amebic Encephalitis (GAE) and Acanthamoeba keratitis (AK). Improving the culture media classically used for this amoeba could help to identify it quickly and facilitate its study as a biological model. The purpose of this study was to compare the growth of two Acanthamoeba genotypes (T3 and T4) in several culture media. Acanthamoeba griffini (T3 genotype) and Acanthamoeba castellanii (T4 genotype) were cultured in PYG, TSY, TYI-S-33, RPMI, and RPMI-FBS medium. The number of amoebas grown in different culture media was counted and compared to each other for 14 days. Findings in this research revealed the highest growth in RPMI-FBS medium. For this reason, we can recommend this culture medium to promote the growth of Acanthamoeba in its biological studies.